2005
DOI: 10.1002/he.183
|View full text |Cite
|
Sign up to set email alerts
|

What campuses need to know about organizational learning and the learning organization

Abstract: This chapter provides an overview of the literature on organizational learning and the learning organization, sets out key concepts in each area, and reviews the way that organizational learning and the learning organization have been applied within higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 12 publications
2
86
0
3
Order By: Relevance
“…The results are consistent with research conducted by DeGeus, 1988;Senge, 1990;Liao & Wu, 2009;Nonaka & Takeuchi, 1995;Su, et al, 2003;Garratt, 1990, Su, et al, 2004Su, et al, 2004;Darroch, 2005;Ke & Wei, 2006;Liao & Wu, 2009. 2) The results showed that OL affects OP. The results are consistent with research conducted by De Geus, 1988;Senge, 1990;Huber, 1991;Dimovski, 1994;Tsang, 1997;Jones & Hendry, 1992;Kezar, 2005;Jones, 2000;Škerlavaj & Dimovski, 2006;Škerlavaj et al, 2007;Liao & Wu, 2009. 3) The results showed that KM affects OP. The results are consistent with research conducted by Škerlavaj & Dimovski, 2006;Wiig, 2002;Gorelick & Monsou, 2005;Liao & Wu, 2009;Darroch, 2005;Alavi & Leidner, 2001;Massey et al, 2002;Schulz & Jobe, 2001;Darroch & McNaughton, 2003;Tanriverdi, 2005;Davenport & Prusak, 1998;Zack, et al, 2009;Mukherjee et al, 1998;Liao & Wu, 2009;Raja Suzana, 2004;2008;Gorelick & Monsou, 2005;…”
Section: Research Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…The results are consistent with research conducted by DeGeus, 1988;Senge, 1990;Liao & Wu, 2009;Nonaka & Takeuchi, 1995;Su, et al, 2003;Garratt, 1990, Su, et al, 2004Su, et al, 2004;Darroch, 2005;Ke & Wei, 2006;Liao & Wu, 2009. 2) The results showed that OL affects OP. The results are consistent with research conducted by De Geus, 1988;Senge, 1990;Huber, 1991;Dimovski, 1994;Tsang, 1997;Jones & Hendry, 1992;Kezar, 2005;Jones, 2000;Škerlavaj & Dimovski, 2006;Škerlavaj et al, 2007;Liao & Wu, 2009. 3) The results showed that KM affects OP. The results are consistent with research conducted by Škerlavaj & Dimovski, 2006;Wiig, 2002;Gorelick & Monsou, 2005;Liao & Wu, 2009;Darroch, 2005;Alavi & Leidner, 2001;Massey et al, 2002;Schulz & Jobe, 2001;Darroch & McNaughton, 2003;Tanriverdi, 2005;Davenport & Prusak, 1998;Zack, et al, 2009;Mukherjee et al, 1998;Liao & Wu, 2009;Raja Suzana, 2004;2008;Gorelick & Monsou, 2005;…”
Section: Research Findingssupporting
confidence: 91%
“…OL tends to focus more on internal concerns for performance and learning as part of condition of human beings within settings. OL tends to focus more on external threats as the reason for fostering learning (Kezar, 2005).…”
Section: The Relationship Betweenmentioning
confidence: 99%
“…That is to say, one test condition for effective SP is whether there is a working degree of consensus on the mission and its elaboration in a given strategic plan. Kezar (2005) accented the role of SP as a vehicle for organizational learning. M. C. Choban, G.…”
Section: Mission and Visionmentioning
confidence: 99%
“…Kezar (2005) noted the value of SP as a process of organizational learning across three phases of exploration, implementation, and evaluation. Her discussion stressed the value of facing skepticism among stakeholders about the value of SP.…”
Section: Inflexible and Formulaic Repetitionmentioning
confidence: 99%
“…KM refers to the process in which organizations assess the data and information that exist within them, and is a response to the concern that people must be able to translate their learning into usable knowledge (Kezar, 2005).…”
Section: Practical Implicationsmentioning
confidence: 99%